Penerapan Metode Jaringan Syaraf Tiruan Untuk Mengetahui Kebenaran Hasil Perkawinan Antar Golongan Darah - NOPRI ADI (JURNAL ILMU PENGETAHUAN & SISTEM INFORMASI (JIPSI), 2018)
ABSTRACT Every human has a blood type. There are four types of human blood groups A, B, AB and O. In medicine, the human blood group classification is done by testing human blood with antigen A and antigen B. blood group could also serve as proof of verification child’s of a couple. This is because the child's blood type consisting of a combination of their parents. the systems, a branch of the neural networks that is perceptron can be applied to determine the truth of the marriage between blood type or inheritance from parent to child’s. The variables used are four blood groups on the cross-model results, the variables of the four blood groups can be separated by one in each a different output. Whereas, the parameter is the target of the marriage with the output we are looking for. If it matches said proven and if it does not it is said not proven. The Neural Network of the algorithm Perceptron consists of a layer of input units, and layers to Output. For input unit will be included husbands blood type and wife blood type are used as a matrix in each of typeface, then made the determination that the target output of the pattern of blood would have been trained in accordance with set targets indicating that blood group managed to prove so the network could ultimately decide the inheritance of blood groups proved or not proved. Keywords: Artificial neural network, perceptron, blood type, inheritance.